DIPLOMASI BUDAYA INDONESIA TERHADAP JEPANG MELALUI RUMAH BUDAYA - Afifah, Muhsinah; Saeri, Mhd. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research analyzes "Indonesia's Cultural Diplomacy Towards Japan Through Rumah Budaya" with the aim of knowing how cultural diplomacy efforts made by the Indonesian government through the Indonesian Cultural House program. Rumah Budaya Indonesia (RBI) is one example of Indonesian diplomacy in Japan. Japan was chosen to strengthen Indonesia's cultural diplomacy because of its significant contribution to Indonesia's growth. In addition, Japan is one of the countries that prioritizes culture as a valuable national resource. In this case, Rumah Budaya Indonesia (RBI) was established in Japan by the Ministry of Education and Culture to support Indonesia's cultural diplomacy as well as one of the instruments in establishing good relations with other countries in achieving national interests. This research uses qualitative and descriptive methods, with reference to the theory of public diplomacy and the idea of cultural diplomacy. The research found that Indonesia uses various cultural diplomacy strategies, including expert exchanges or studies, exhibitions, and competitions, to carry out its diplomacy through RBI. The results of this study prove that in strengthening cultural diplomacy conducted by Indonesia towards Japan, it has succeeded in increasing the positive impression and interest of Japanese people towards Indonesian culture. Keywords: Rumah Budaya Indonesia, Cultural Diplomacy, Public Diplomacy